2017
DOI: 10.1097/mbc.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Gingival bleeding and mild type 1 von Willebrand disease

Abstract: Oral bleeding is a frequently reported symptom of von Willebrand disease (VWD) and evaluated by several VWD bleeding scores. Gingival bleeding is also known to be a leading symptom of plaque-induced gingivitis and untreated periodontal disease. This study evaluates whether mild type 1 VWD is associated with an increased susceptibility to gingival bleeding. In this case-control study, 50 patients and 40 matched controls were periodontally examined, answered a questionnaire, and underwent professional teeth clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…[ 21 ] However, other scholars have suggested that gingival bleeding in VWD patients may be caused by gingival inflammation rather than a real symptom. [ 22 ] In this case, there was no uncontrollable bleeding during periodontal treatment, and the blood routine examination showed normal coagulation function. It is speculated that the child still has vwf gene mutation but does not show any symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…[ 21 ] However, other scholars have suggested that gingival bleeding in VWD patients may be caused by gingival inflammation rather than a real symptom. [ 22 ] In this case, there was no uncontrollable bleeding during periodontal treatment, and the blood routine examination showed normal coagulation function. It is speculated that the child still has vwf gene mutation but does not show any symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have proven that hemophilic patients exhibit higher index values of gingival bleeding, plaque accumulation, and increased numbers of teeth affected by carious processes/extractions [20]. Nevertheless, no direct interrelationship has been detected between VWD and periodontal inflammation, as a reaction to the microorganism aggregation [17][18][19]. Another important aspect that should be considered is circulating blood cells profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Weickert et al 2014 [17], BOP showed no major difference between the VWD group (14.5 ± 10.1%) and control (12.3 ± 5.3%). Weickert and coworkers 2017 [18], obtained BoP values of 17.0 ± 7.2% for the VWD group and 17.2 ± 7.6% for the control group. Epping et al [19] obtained BoP values of 14.5 ± 10.1% for the VWD group and 12.3 ± 5.3% for the control group.…”
Section: Qualitative Synthesismentioning
confidence: 92%